PENGINDERAAN JAUH SISTEM THBRMAL UNTUK MENGETAHUI PERSEBARAN PANASBUMI DI NGEBEL, KABUPATEN PONOROGO, PROVINSI JAWA TIMUR - , INGGRID ERNESIA, Drs. Retnadi Heru Jatmikoo M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Method of extracting information about land surface temperatures have been carried out and applied to specific purpose. In geographic, information extraction temperature is usually done for pure research in the field of remote sensing and integration with Geographic Information System to see the anomalous heat in the earth surface. Geothermal studies using Landsat imagery is still not ubiquitous. Most of the preliminary surveys in geothermal exploration is still using terrestrial approach to determine potential areas of geothermal. This study aimed to determine the ability of the thermal channel on Landsat TM imagery to identify the distribution of geothermal in Ngebel and also to determine the appearance of objects associated with the surface geology geothermal system, among other geological structures, lithologies, and geothermal sites based on digital image processing of Landsat TM. Location of the study focused on temperature appear prominently on the image processing results information extraction temperature and geological interpretation of a rock unit and structures of geology. Digital image processing performed include contrast enhancement, filtering, composite image and information extraction temperature. The results of this research indicate that the extraction of temperature information band 6 is present the appearance of the surface temperature in Ngebel and it also present the appearance of geothermal manifestations. Landsat TM images were processed using digital image processing to recognize the appearance of the objects surface geology well. Distribution of geothermal potential in Ngebel as dots for potential geothermal energy.The existence of geological structures controlling the appearance of the surface geothermal manifestations.